2011
DOI: 10.2215/cjn.09051209
|View full text |Cite
|
Sign up to set email alerts
|

Modified C-Reactive Protein Might be a Target Autoantigen of TINU Syndrome

Abstract: SummaryBackground and objectives The cross-reactive antigen(s) of tubulointerstitial nephritis and uveitis (TINU) syndrome from renal tubulointerstitia and ocular tissue remain unidentified. The authors' recent study demonstrated that the presence of serum IgG autoantibodies against modified C-reactive protein (mCRP) was closely associated with the intensity of tubulointerstitial lesions in lupus nephritis. The study presented here investigates the possible role of IgG autoantibodies against mCRP in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
2
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 25 publications
4
105
2
9
Order By: Relevance
“…A limitation of this test is that mCRP-Ab can be detected in several other chronic diseases such as SLE (29,30) and chronic hepatitis C infection (31). We also identified some discrepancy between the normative value of mCRP-Ab in this study compared with our previous report (21). We speculate that this discrepancy was likely due to the instability of mCRP-Ab in the serum sample from the SLE patient (positive control) that had been stored for 2 years at 280°C.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…A limitation of this test is that mCRP-Ab can be detected in several other chronic diseases such as SLE (29,30) and chronic hepatitis C infection (31). We also identified some discrepancy between the normative value of mCRP-Ab in this study compared with our previous report (21). We speculate that this discrepancy was likely due to the instability of mCRP-Ab in the serum sample from the SLE patient (positive control) that had been stored for 2 years at 280°C.…”
Section: Discussioncontrasting
confidence: 75%
“…We showed that late-uveitis TINU was clinically and pathologically indistinguishable from DATIN at biopsy. We previously reported that mCRP-Ab might be useful in distinguishing patients with TINU from patients with DATIN (21). In this study, of patients diagnosed with DATIN, those who went on to develop late-onset uveitis (i.e., TINU misclassified as DATIN), had higher levels of mCRP-Ab compared with those who had true DATIN.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We have previously regarded anti-CRP antibodies as rather specific for SLE, but this study and others clearly show that this does not hold true [16,36,37]. On the other hand, SLE and chronic HCV infection share several disease characteristics.…”
Section: Discussioncontrasting
confidence: 58%
“…Accordingly, mCRP has been detected on circulating microparticles [81] and the discovery of RNA aptamers specifically recognizing mCRP [85] may eventually result in the development of clinical assays for mCRP. Alternatively, autoantibodies against mCRP that were found to be correlated with autoimmune [86][87][88] and heart diseases [89] could be regarded as an indirect index to measure global mCRP production.…”
Section: Dissociation Of Crp Localizes the Enhanced Bioactivitiesmentioning
confidence: 99%